Phosphodiesterase 5 Inhibitor Use in Men With Hypertrophic Cardiomyopathy - Ruzek, Lukas; Konecny, Tomas; Soucek, Filip; Konecny, Dana; Mach, Lukas; Ommen, Steve R; Kopecky, Stephen L; Nishimura, Rick A (The American journal of cardiology, 2015)
The prevalence of sexual dysfunction (SD) in men with hypertrophic cardiomyopathy (HC) remains unknown, yet its clinical relevance may be high given that its treatment-phosphodiesterase 5 inhibitors (PDE5i)-can increase the left ventricular outflow tract pressure gradient. In this retrospective study, we evaluated the medical records of consecutively seen men with HC for the evidence of SD (defined as SD diagnosis noted in the medical record, the use of medications unique for SD, or SD reported by the patient on a routine clinical questionnaire). Of the 283 consecutively seen men with HC (mean age 52.9 ± 14.1 years), 63 patients (22%) with SD were identified. Of those with SD, 38% were recorded as regularly using PDE5i. In conclusion, SD and the use of PDE5i present a relatively common occurrence in men with HC, and further studies are needed to develop an evidence-guided algorithm for safe implementation of SD therapies in this most common inherited cardiomyopathy.
Keywords: dospělí; inhibitory fosfodiesterasy 5; Prevalence; beta blokátory; Adult; lidé; hypertrofická kardiomyopatie; Cardiomyopathy, Hypertrophic; Risk Factors; prevalence; retrospektivní studie; sexuální dysfunkce fyziologická; Male; Phosphodiesterase 5 Inhibitors; Aged; rizikové faktory; Sexual Dysfunction, Physiological; Adrenergic beta-Antagonists; lidé středního věku; senioři; mužské pohlaví; Retrospective Studies; Middle Aged; Humans